Cerebral Salt Wasting Syndrome - Mehmet Salih Sevdi; Kerem Erkalp; Eyüp Sabri Akagündüz; Aydın Fırıncıoğlu; Ayşin Selcan (Galenos Yayinevi, 2016)
A serum sodium (Na) value below 135 mEq/L is evaluated as hyponatremia. Hyponatremia is the most common electrolyte abnormality observed in hospitalized patients in particular. Hypovolemic hypoosmolar hyponatremia is the most frequent clinical table. One of the reasons of this is cerebral salt-wasting syndrome (CSWS). CSWS is a rare condition progressing with low plasma osmolality, urine osmolality above 100-150 mOsm/kg and urine- Na concentration above 20 mEq/L. In the blood and urine sample analysis performed upon sudden loss of consciousness on the 15th day of the intensive care unit follow-up of 79-year-old female patients due to falling from stairs, blood biochemistry Na value was 120 mEq/L, plasma osmolality was 250 mOsm/kg, urine Na value was 180 mEq/L, urine osmolality was 1200 mOsm/kg, urine diuresis was >3 mL/kg/hour. The central venous pressure was 2 mmHg. The patient, considered to be diagnosed with CSWS, was treated with 9% NaCl and 3% hypertonic saline solution. Her clinical course was improved on the 18th day. She died on the 81st day secondary to septicemia in the subsequent follow-up. In this article, it was aimed to report a patient with CSWS which progresses with low percentage in intensive care unit patients with head trauma, is frequently confused with inappropriate antidiuretic hormone syndrome and progresses mortally when not diagnosed distinctively well.